A institucionalização da responsabilidade social corporativa em distribuidoras de energia elétrica - Santos, Tatiana Márcia de Sabóia (2008)
Using the institutional theory as a base, more specifically the process of institutionalization proposed by Tobert and Zucker, this work has as a general objective the investigation of the process of institutionalization of the social responsibility in distributors of electricity, beginning with the study of the electric companies in the states of Ceara and Bahia. Considering the objective of this study, the research is exploratory-descriptive. Direct and indirect methods of research were used with a foundation in bibliographical and documentary research of the division of distribution of electricity in Brazil. Besides this, multi-case studies were used in studying COELCE (Companhia Energética do Ceará) and COELBA (Companhia de Eletricidade da Bahia) using interviews and questionnaires of those involved in the process of institutionalizing the RSC of these companies. In approaching the problem, the research was qualitative, and the method of studying the object was monographic. The analysis of the data was done by analyzing the content and documentation. The results of the study show that, within the stages of the process of institutionalization proposed by Tobert and Zucker (1999), both companies were in the phase of sedimentation of RSC, which passes the positive impacts observed, the resistance of opposing groups, as well as in defense of the interested groups.